1983
DOI: 10.1520/jfs12249j
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sex with a Discriminant Analysis of New Pelvic Bone Measurements: Part I

Abstract: The pelves of 100 black skeletons were measured on both sides for the following: (1) length from the superiormost aspect of the pubic symphysis to the nearest rim of the acetabulum (PS-A), (2) length from the highest point of the pubic tubercle to the nearest rim of the acetabulum (PT-A), (3) acetabular diameter (AD), (4) the vertical distance from the anterior aspect of the ischial tuberosity to the farthest rim of the acetabulum (IT-A), and (S) greatest femur head diameter. From these, three indices were der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 4 publications
2
39
0
Order By: Relevance
“…Therefore, awareness of the average dimensions of the hip bone in both sexes will also help in early detection of disputed sex by forensic experts. 2 In the past, many workers have evolved various metrical parameters and indices for sexing of hip bone, Derry,3 Sraus, 4 Jovanovic and Zivanovic, 5 Jovanovic et al, 6 Singh and Potturi, 7 Schulter Ellis, 8 Turner, 9 Pal et al 10 Racial differences in Thais, Chinese, Nigerians and other and Msamati et al 12 Various metrical parameters for hip bone have also been reported by Washburn et al 13 and Davivongs et al…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, awareness of the average dimensions of the hip bone in both sexes will also help in early detection of disputed sex by forensic experts. 2 In the past, many workers have evolved various metrical parameters and indices for sexing of hip bone, Derry,3 Sraus, 4 Jovanovic and Zivanovic, 5 Jovanovic et al, 6 Singh and Potturi, 7 Schulter Ellis, 8 Turner, 9 Pal et al 10 Racial differences in Thais, Chinese, Nigerians and other and Msamati et al 12 Various metrical parameters for hip bone have also been reported by Washburn et al 13 and Davivongs et al…”
Section: Introductionmentioning
confidence: 99%
“…The modified ischiopubic index, using the acetabulum rim instead of the central acetabular point, identified sex with an accuracy of approximately 95% or greater (Thieme and Schull, 1957;Richman et al, 1979;Kimura, 1982;Novotný, 1986). The acetabulopubic index, which is a variant of the modified ischiopubic index, diagnosed sex with an accuracy of over 90% (Schulter-Ellis et al, 1983). These indices that take advantage of the greater proportion of the pubis in the female pelvis, and are known to be more accurate in the determination of sex than the parameters based on the sciatic notch.…”
Section: Introductionmentioning
confidence: 99%
“…Because the trend for an outline to be more or less oval or triangular is difficult to visually assess and because there is an infinite number of transitional shapes, only a precise quantitative approach such as Fourier analysis allows for unambiguous characterization and statistical analysis. The pelvis is considered to be the part of the human skeleton, which presents the greatest sexual dimorphism (Martin, 1914;Washburn, 1948Washburn, , 1949Jovanovic and Zivanovic, 1965;Bass, 1969;Phenice, 1969;Palfrey, 1974;Singh and Potturi, 1978;Schulter-Ellis et al, 1983; MacLaughlin and Bruce, 1986, 1990;Lovell, 1989;Tague, 1989Tague, , 1992Anderson, 1990;Sutherland and Suchey, 1991;Arsuaga and Carretero, 1994;Rogers and Saunders, 1994;Luo, 1995;Fuller, 1998;Bruzek, 2002;Gü lekon and Turgut, 2002;Patriquin et al, 2002Patriquin et al, , 2003Patriquin et al, , 2005Uberlaker and Volk, 2002; Igbigbi and NanonoIgbigbi, 2003;Rissech et al, 2003;Walker, 2005;Steyn and Iscan, 2008;Vlak et al, 2008). Among the numerous pelvic traits presenting sex differences, the obturator foramen (foramen obturatum; also formerly named: thyroid foramen, oval foramen, ischiopubic foramen, or subpubic foramen) is regularly cited.…”
mentioning
confidence: 99%